Identification and antibiotic control of endophytic bacteria contaminants in micropropagated potato explants - Pereira, Jonny Everson Scherwinski; Mattos, Maria Laura Turino; Fortes, Gerson Renan de Luces (Pesquisa Agropecuaria Brasileira, 2003)
This work aimed to isolate, characterize and identify contaminant endophytic bacteria found in potato tissues during the micropropagation and to select antibiotics for in vitro control of these microorganisms by determining the inhibitory minimal bactericidal concentration. Potato shoots presenting bacterial contamination during the in vitro multiplication were superficially sterilized and the internodes transferred to Petri dishes with nutrient agar medium for up to five days at 28°C. After subcultures the grown bacteria were purified and identified through taxonomic tests. A total of eight bacterial endophytic strains were isolated and identified as belonging to Acetobacteriaceae (1) and Enterobacteriaceae (2) families and Corynebacterium (3), Pseudomonas (1) and Xanthomonas (1) genera. The best results for bacterial growth inhibition were obtained with ampicilin, chloramphenicol, streptomycin and tetracycline antibiotics in concentrations ranging from 32 to 256 mg L-1.
Keywords: Solanum tuberosum; contamination; micropropagation; tissue culture; microorganisms